Stanley Cavell polítical readings: The reivindication of joy in the commitment for justice - Lastra, Antonio; Peris-Cancio, José-Alfredo (Analysis. Journal of Philosophical Research, 2019)
Stanley Cavell's philosophy does not properly develop a political theory. Its Socratic method proposes precisely to review the language with which the community is configured. That is the most genuine contribution of philosophy, which has to find its space in the face of speeches made in tune with political power and that ultimately reduces participation in the formation of the common good. Facing properly the tragedy of skepticism should lead to suspicion of a modern philosophy that does not respond to the concerns of citizens and is imposed in the public sphere restricting the possibility of a rational critique of their postulates. Demanding the opening of philosophy to other expressive forms of reason such as literature, opera or cinema can correct that reduction. Faced with the dominant proposal that, starting with Rawls, seeks to establish the predominance of rules and economic benefits, Cavell proposes a return to politics that seeks the joy of people as an expression of true democracy.